2021
DOI: 10.1002/trc2.12138
|View full text |Cite
|
Sign up to set email alerts
|

Person‐centered assessment of people living with dementia: Review of existing measures

Abstract: Introduction Person‐centered care and assessment calls for measurement tools that help researchers and providers understand people with dementia, their social relationships, and their experience of the care environment. This paper reviewed available measures and evaluated their psychometric properties. Methods Literature searches of major databases (PsycInfo, PubMed, EBSCO, CINAHL) for papers examining person‐centered constructs in samples of people living with dementia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 80 publications
1
8
0
Order By: Relevance
“…As stated, the citizenship approach acknowledges that people are embedded in and shaped by a sociocultural context. Thus, everyday life incorporates both the social and physical environment [ 134 ]. This underlines the socio-relational and embodied-material approach described by Ward et al [ 135 ].…”
Section: Discussionmentioning
confidence: 99%
“…As stated, the citizenship approach acknowledges that people are embedded in and shaped by a sociocultural context. Thus, everyday life incorporates both the social and physical environment [ 134 ]. This underlines the socio-relational and embodied-material approach described by Ward et al [ 135 ].…”
Section: Discussionmentioning
confidence: 99%
“…To expand on this effort, TRCI has put forth a Call for Papers on Key Issues in Measurement, hoping to include topics such as person‐centered measures that foster a constructive balance between strengths and deficits assessment; evidence‐based tools to guide structures and processes of care; community‐centric measures and measures for long‐term care and international use; measures recognizing diversity and issues of racism, stigma, and discrimination; and stakeholder engagement in measurement development. Already, the special collection includes papers on reconsidering frameworks for dementia care, 10 measures for dementia care planning, 11 and person‐centered assessment; 12 a paper on environmental assessment tools is currently in press. 13 Upcoming papers will overview and evaluate measures related to detection and diagnosis and activities of daily living; discuss goal attainment scaling as a person‐centered measurement tool useful across individuals and the course of the disease; address recruitment and engagement in dementia research; and explore the operationalization of person‐centered care in practice.…”
Section: Tablementioning
confidence: 99%
“…Historically, providers have neglected the perspective of people living with dementia, based upon the faulty assumption that people with dementia cannot provide reliable and valid reports on their experiences, needs, values, and preferences. A recent analysis by Mast and colleagues (Mast et al, 2021) found a wide range of self-report instruments that demonstrated adequate psychometric properties in people living with dementia. These included constructs hope, psychological well-being, meaning, resilience, spirituality, social support, stigma, and care preferences.…”
Section: Assessment Domainsmentioning
confidence: 99%
“…Social rejection Internalized shame Financial insecurity Social isolation 24 self-report items Note. Source: Mast et al (2021).…”
Section: Emotionmentioning
confidence: 99%